Social comparison and envy on social media: A critical review. (June 2022) - Meier, Adrian; Johnson, Benjamin K.
Abstract: There is both public and scholarly concern that (passive) social media use decreases well-being by providing a fertile ground for harmful (upward) social comparison and envy. The present review critically summarizes evidence on this assumption. We first comprehensively synthesize existing evidence, including both prior reviews and the most recent publications (2019–2021). Results show that earlier research finds social comparison and envy to be common on social media and linked to lower well-being. Yet, increasingly, newer studies contradict this conclusion, finding positive links to well-being as well as heterogeneous, person-specific, conditional, and reverse or reciprocal effects. The review identifies four critical conceptual and methodological limitations of existing evidence, which offer new impulses for future research. Highlights: Social media (SM) supposedly make social comparison, envy, and well-being worse. This review finds mixed and inconsistent evidence for this claim. Earlier studies show comparisons and envy are common on SM and linked to ill-being. Recent studies find positive, person-specific, conditional, and reciprocal effects. Specific causes, online/offline differences, and user agency remain open questions.